Pengaruh Ukuran Partikel Bentonit dan Arang Kayu pada Pembuatan Keramik Filter - Widayati W; Adi Ilcham; Trenggono Nur Adiguna; Hanurizal Himawari Hashari (Seminar Nasional Teknik Kimia Kejuangan, 2016)
Ceramic filter is one of the alternative can be used as filter media. Ceramic filter can be made from materials such as clay, river sand mixed with some charcoal and bentonite. Charcoal and bentonite were chosen for this research, because both of them are selective adsorben, have wide surface area, and high adsorption rate. Making the ceramic filter needs material with certain particle size of (-10+30)mesh,(-50+80)mesh, (-80+100)mesh, and (-100+200)mesh. The process of making sample of the filter were done using slip casting method, which consist of mixing all of the homogenic materials with water, and then mold it as needed. Then the filter is dried for 1 day, and then burned in the furnace with 650oC for 2,5 hour, and then let it cool down inside the furnace for ± 24 hour. The sample filter will be tested in various category such as porosity, flux, and pressure test. Finally, the ceramic filter will be tested with the turbidity of the river water in Giwangan. The optimal composition in this research is -100+200 mesh with 70%:30% of bentonite and charcoal, with the result of 10,05KN pressure value, 22,742% porosity, 0,2ml/cm2 flux, and the reduction of turbidity around 50,72%.